2006
DOI: 10.1038/sj.npp.1301062
|View full text |Cite
|
Sign up to set email alerts
|

Addiction-Related Alterations in D1 and D2 Dopamine Receptor Behavioral Responses Following Chronic Cocaine Self-Administration

Abstract: The cocaine-addicted phenotype can be modeled in rats based on individual differences in preferred levels of cocaine intake and a propensity for relapse in withdrawal. These cocaine-taking and -seeking behaviors are strongly but differentially regulated by postsynaptic D 1 and D 2 receptors in the mesolimbic dopamine system. Thus, we determined whether addiction-related differences in cocaine selfadministration would be related to differential sensitivity in functional D 1 and D 2 receptor responses. Using a p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
80
0

Year Published

2006
2006
2011
2011

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 83 publications
(92 citation statements)
references
References 46 publications
12
80
0
Order By: Relevance
“…When saline was initially substituted for cocaine in this study, the control rats showed 'extinction burst' responding, which is commonly observed in actively learned responses (Harris et al, 2007), whereas the vaccinated rats did not. This observation is very similar to observations of 'extinction burst' responding in rats with high cocaine intake and no 'extinction bursts' in rats with low cocaine intake (Edwards et al, 2007). In addition, when primed with cocaine, control rats reinstated responding on the previously cocaineassociated lever, whereas vaccinated rats did not, consistent with a previous finding (Carrera et al, 2000).…”
Section: Discussionsupporting
confidence: 89%
“…When saline was initially substituted for cocaine in this study, the control rats showed 'extinction burst' responding, which is commonly observed in actively learned responses (Harris et al, 2007), whereas the vaccinated rats did not. This observation is very similar to observations of 'extinction burst' responding in rats with high cocaine intake and no 'extinction bursts' in rats with low cocaine intake (Edwards et al, 2007). In addition, when primed with cocaine, control rats reinstated responding on the previously cocaineassociated lever, whereas vaccinated rats did not, consistent with a previous finding (Carrera et al, 2000).…”
Section: Discussionsupporting
confidence: 89%
“…It is not clear, therefore, which of the many behavioral and psychological consequences of cocaine self-administration are due to changes in dorsal striatal D2 High receptors. Seeman and his colleagues (2002,2007) have reported that sensitization to amphetamine is associated with an increase in D2 High receptors, and both experimenter-administered cocaine and cocaine self-administration experience have been reported to produce behavioral supersensitivity to a challenge injection with a direct D2 receptor agonist (De Vries, et al, 2002, Edwards, et al, 2007. It has also been reported that both the limited and extended access cocaine self-administration procedures used in the current study produce psychomotor sensitization (Ferrario, et al, 2005, Knackstedt andKalivas, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…However, a long-standing puzzle in this area is that preclinical studies have consistently found that rats treated with amphetamine or cocaine, and then withdrawn, are hypersensitive to the psychomotor activating and incentive motivational effects of these "indirect agonists" (Robinson and Berridge, 1993), and even more importantly, to the psychomotor effects of direct-acting D2 agonists (Ujike, et al, 1990, De Vries, et al, 2002, Edwards, et al, 2007. Studies examining the effects of cocaine treatment on D2 receptor binding in rodents are mixed, with reports of increases (Trulson andUlissey, 1987, Peris, et al, 1990), decreases (Kleven, et al, 1990, Maggos, et al, 1998 or no change (Dwoskin, et al, 1988, Claye, et al, 1995.…”
Section: Introductionmentioning
confidence: 99%
“…Further research is needed to determine if higher doses of cocaine suppress cocaine responding, as observed in preclinical investigations, though these initial data raise questions as to the relationship between cocaine dose, craving, and drug-seeking behavior. For example, one particular study found that higher doses of cocaine suppress cocaine responding (# injections/session), though total cocaine intake remains similar (mg/kg/session) (Edwards et al, 2006).…”
Section: Discussionmentioning
confidence: 99%